Deliberative Teaching as an Emergent Field: The Challenge of Articulating Diverse Research Agendas to Promote Educational Experiences for Citizenship - Larrain, Antonia; Fortes, Gabriel; Rojas, María Teresa (Frontiers in Psychology, 2021)
Democracies are increasingly dependent upon sustainable citizenship, that is, active participation and engagement with the exercising of rights in a field of plural interests, often contradictory and in conflict. This type of citizenship requires not only social inclusion, habits of knowledge, and evidence-based reasoning but also argumentation skills, such as the individual and social capacity to dispute and exercise individual and social rights, and to deal peacefully with sociopolitical conflict. There is empirical evidence that educational deliberative argumentation has a lasting impact on the deep and flexible understanding of knowledge, argumentation skills, and political and citizenship education. However, these three trends of research have developed independently with insufficient synergy. Considering the relevance of deliberative education for contemporaneous democracies and citizenship, in this paper we seek to converge in a field of interlocution, calling it deliberative teaching. Our aim is to propose a way to increase the dialog and collaboration between the diffuse literature on argumentation and education, highlighting both the main theoretical and empirical gaps and challenges that remain and the possibilities to advance our knowledge and the educational impact that this integrating field could offer.